KDM2B regulates choline kinase expression and neuronal differentiation of neuroblastoma cells - Domizi, Pablo (2019)
Fil: Fil: Domizi, Pablo. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.